To simplify the expression, let's start by applying the distributive property:
1/2 (x + 4) = 1/2 * x + 1/2 * 4 = 1/2 * x + 2
1/4 (4x - 2) = 1/4 * 4x + 1/4 * (-2) = 1x - 1/2
Now we can combine like terms:
1/2 x + 2 + 1x - 1/2 = (1/2 x + 1x) + (2 - 1/2) = (3/2)x + 3/2 = 3/2(x + 1)
Therefore, the simplified expression is 3/2(x + 1).
Add: 1/2 (x + 4) + 1/4 (4x - 2). Answer should be in mixed number form.
14 answers
Is that in mixed number form??
Apologies for the confusion. Let's convert the expression to mixed number form.
Starting with the simplified expression: 3/2(x + 1)
We can distribute the 3/2 to get: 3/2 * x + 3/2 * 1
3/2 * x = 3/2x
3/2 * 1 = 3/2
Combining these terms, we have: 3/2x + 3/2
To write this in mixed number form, we need to convert the improper fraction (3/2) to a mixed number.
Dividing 3 by 2, we get 1 with a remainder of 1. This remainder becomes the numerator, and the divisor becomes the denominator.
Thus, the mixed number form of the expression is: 1 1/2x + 1 1/2.
Starting with the simplified expression: 3/2(x + 1)
We can distribute the 3/2 to get: 3/2 * x + 3/2 * 1
3/2 * x = 3/2x
3/2 * 1 = 3/2
Combining these terms, we have: 3/2x + 3/2
To write this in mixed number form, we need to convert the improper fraction (3/2) to a mixed number.
Dividing 3 by 2, we get 1 with a remainder of 1. This remainder becomes the numerator, and the divisor becomes the denominator.
Thus, the mixed number form of the expression is: 1 1/2x + 1 1/2.
Add (4d - 3) + (12d + 4)
To add (4d - 3) + (12d + 4), we can combine like terms:
4d + 12d = 16d
-3 + 4 = 1
Therefore, the sum is 16d + 1.
4d + 12d = 16d
-3 + 4 = 1
Therefore, the sum is 16d + 1.
Add (2m - 3) + (3n - 1) + (3m + 1)
To add (2m - 3) + (3n - 1) + (3m + 1), we can combine like terms:
2m + 3m = 5m
-3 + 1 = -2
The term (3n) does not have any like terms to combine with, so it remains as is.
Therefore, the sum is 5m + 3n - 2.
2m + 3m = 5m
-3 + 1 = -2
The term (3n) does not have any like terms to combine with, so it remains as is.
Therefore, the sum is 5m + 3n - 2.
That was wrong 😞
Apologies for the mistake. Let's redo the addition correctly.
(2m - 3) + (3n - 1) + (3m + 1)
Combining like terms:
2m + 3m = 5m
-3 + 1 + 1 = -1
For (3n), since there are no other n terms to combine with, it remains as is.
Therefore, the correct sum is 5m + 3n - 1.
(2m - 3) + (3n - 1) + (3m + 1)
Combining like terms:
2m + 3m = 5m
-3 + 1 + 1 = -1
For (3n), since there are no other n terms to combine with, it remains as is.
Therefore, the correct sum is 5m + 3n - 1.
That’s still wrong
Apologies for the repeated errors. Let's do the addition correctly this time:
(2m - 3) + (3n - 1) + (3m + 1)
Combining like terms:
2m + 3m + 3m = 8m
-3 - 1 + 1 = -3
For (3n), since there are no other n terms to combine with, it remains as is.
Therefore, the correct sum is 8m + 3n - 3.
(2m - 3) + (3n - 1) + (3m + 1)
Combining like terms:
2m + 3m + 3m = 8m
-3 - 1 + 1 = -3
For (3n), since there are no other n terms to combine with, it remains as is.
Therefore, the correct sum is 8m + 3n - 3.
Your STILL wrong
I apologize for the continued errors. Let's try again and double-check our work:
(2m - 3) + (3n - 1) + (3m + 1)
Combining like terms:
2m + 3m = 5m
-3 + 1 + 1 = -1
For (3n), since there are no other n terms to combine with, it remains as is.
Therefore, the correct sum is 5m + 3n - 1.
(2m - 3) + (3n - 1) + (3m + 1)
Combining like terms:
2m + 3m = 5m
-3 + 1 + 1 = -1
For (3n), since there are no other n terms to combine with, it remains as is.
Therefore, the correct sum is 5m + 3n - 1.
The answer is 5m+3n-3